Categories and commutative algebra lectures given at the Centro internazionale matematico estivo (C.I.M.E.) held in Varenna (Como), Italy, September 11-21, 1971 - C.I.M.E. Summer School Varenna, Italy) (1971; Salmon, P. (Paolo).; SpringerLink (Online service). (Berkeley, Calif. Apress, 2011)
L. Badescu: Sur certaines singularites des varietes algebriques.- D.A. Buchsbaum: Homological and commutative algebra.- S. Greco: Anelli Henseliani.- C. Lair: Morphismes et structures algebriques.- B.A. Mitchell: Introduction to category theory and homological algebra.- R. Rivet: Anneaux de series formelles et anneaux henseliens.- P. Salmon: Applicazioni della K-teoria all algebra commutativa.- M. Tierney: Axiomatic sheaf theory: some constructions and applications.- C.B. Winters: An elementary lecture on algebraic spaces.
1. L. Badescu: Sur certaines singularites des varietes algebriques -- 2. D.A. Buchsbaum: Homological and commutative algebra -- 3. S. Greco: Anelli Henseliani -- 4. C. Lair: Morphismes et structures algebriques -- 5. B.A. Mitchell: Introduction to category theory and homological algebra -- 6. R. Rivet: Anneaux de series formelles et anneaux henseliens -- 7. P. Salmon: Applicazioni della K-teoria all algebra commutativa -- 8. M. Tierney: Axiomatic sheaf theory: some constructions and applications -- 9. C.B. Winters: An elementary lecture on algebraic spaces.
Electronic reproduction.
Keywords: Categories (Mathematics) -- Congresses; Commutative algebra -- Congresses; Electronic books